State social policy towards the disabled and elderly in rural areas of the RSFSR in the 1920s-1930s: Ideas and everyday practices - Alexander S. Kovalev (Крестьяноведение, 2025)
The article considers the main principles of the Soviet social policy towards disabled peasants in the 1920s–1930s, when they were the least protected category of citizens. The disabled in cities had priority in receiving state social assistance, while “disabled peasants” were supported on a residual basis. The leading actor of social policy in rural areas was peasant mutual-aid committees (peasant committees) which worked from 1921 to 1930. These committees were primarily responsible for providing social support to disabled rural residents. On the one hand, they were to receive the same types of social assistance as urban residents: pension, one-time financial and in-kind assistance, prosthetics, and employment opportunities. On the other hand, disabled and elderly peasants faced class, social and age-based discrimination when trying to get what was due. In addition to practices of social assistance, in the 1920s– 1930s, there were various projects aimed at improving the social situation of the disabled in rural areas. However, most of such ideas focused on the remaining work capacity of the disabled and elderly, including in collective farms. With the beginning of collectivization, peasant mutual-aid committees were replaced by mutual-aid funds, and the responsibility for supporting the disabled and elderly was given to the working population of collective farms. Due to the lack of sufficient financial resources in collective farms, the disabled and elderly were also assigned work tasks which often ignored their capabilities. The author makes a conclusion about low efficiency of the state social policy measures and low level of satisfaction of the real needs of the disabled and elderly in the village.